Multimicrojoule GaSe-based midinfrared optical parametric amplifier with an ultrabroad idler spectrum covering 4.2-16 μm - Liu, Kun (2021)
We report a multimicrojoule, ultrabroadband midinfrared optical parametric amplifier based on a GaSe nonlinear crystal pumped at ∼2  μm. The generated idler pulse has a flat spectrum spanning from 4.5 to 13.3 μm at -3  dB and 4.2 to 16 μm in the full spectral range, with a central wavelength of 8.8 μm. The proposed scheme supports a subcycle Fourier-transform-limited pulse width. A (2+1)-dimensional numerical simulation is employed to reproduce the obtained idler spectrum. To our best knowledge, this is the broadest -3  dB spectrum ever obtained by optical parametric amplifiers in this spectral region. The idler pulse energy is ∼3.4  μJ with a conversion efficiency of ∼2% from the ∼2  μm pump to the idler pulse.